2021
DOI: 10.1073/pnas.2102914118
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structural variants constrain and facilitate adaptation in natural populations of Theobroma cacao , the chocolate tree

Abstract: Genomic structural variants (SVs) can play important roles in adaptation and speciation. Yet the overall fitness effects of SVs are poorly understood, partly because accurate population-level identification of SVs requires multiple high-quality genome assemblies. Here, we use 31 chromosome-scale, haplotype-resolved genome assemblies of Theobroma cacao—an outcrossing, long-lived tree species that is the source of chocolate—to investigate the fitness consequences of SVs in natural populations. Among the 31 acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 63 publications
8
68
0
Order By: Relevance
“…Given the lack of knowledge about inversion rates in natural conditions and the computation challenge represented by the simulation of complex patterns of recombination, we used reasonably high inversion rates in our sex-chromosome evolution simulations, making it possible to observe the stepwise extension of a nonrecombining region within 100,000 generations. Recent studies suggested that inversions may not be too rare and that inversion breakpoints may be widely distributed throughout the genome [ 51 , 69 71 ]. The use of different inversion rates might result in much shorter or much longer times for the stepwise extension of the nonrecombining region, but should not change the final outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of knowledge about inversion rates in natural conditions and the computation challenge represented by the simulation of complex patterns of recombination, we used reasonably high inversion rates in our sex-chromosome evolution simulations, making it possible to observe the stepwise extension of a nonrecombining region within 100,000 generations. Recent studies suggested that inversions may not be too rare and that inversion breakpoints may be widely distributed throughout the genome [ 51 , 69 71 ]. The use of different inversion rates might result in much shorter or much longer times for the stepwise extension of the nonrecombining region, but should not change the final outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, genome-graph based approaches were particularly relevant, allowing us to build a variation-aware reference graph (Garrison et al, 2018), and then perform unbiased mapping of reads to this graph (Sirén et al, 2020). Such two-step approaches have also be used in a handful of studies looking at SVs in chocolate trees Theobroma cacao (Hämälä et al, 2021), soybeans Glycine max (Lemay et al, 2021), and potato beetle Leptinotarsa decemlineata (Cohen, Hawthorne, & Schoville, 2021). Based on this, we believe that the combination of 2 nd and 3 rd generation sequencing is promising to study structural polymorphism within a population genomics framework and will allow the inclusion of SVs in studies of speciation and adaptation genomics.…”
Section: Discussionmentioning
confidence: 99%
“…WGS has also been used to provide a complete picture of genetic variation within a population including structural variants (SV) and presence-absence variation (PAV) ( Pinosio et al, 2016 ; Wang et al, 2018 ). Recent research has demonstrated the impact of SV and PAV on important phenotypic variation observed between cultivars and adaptative trait variation including disease resistance ( Zhou et al, 2019 ; Hämälä et al, 2021 ). SnS experiments show potential to detect genetic variation linked to selection and adaptation in experimentally generated populations ( Schlötterer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%